Smoking and promoter-specific deoxyribonucleic acid methylation of the atrial natriuretic peptide gene: methylation of smokers and non-smokers differs significantly during withdrawal - Glahn, Alexander; Schuster, Rilana (European addiction research, 2017)
Background: Atrial natriuretic peptide (ANP) is well known in psychiatric disorders to modulate hypothalamic-pituitary-adrenal axis activity. Disturbances of ANP have been described in early abstinent alcohol-dependent patients. This is the first longitudinal investigation on cytosine-phosphatidyl-guanine (CpG)-island promoter methylation of the ANP gene in the blood of tobacco-dependent patients. Methods: In a longitudinal approach, we investigated whether changes in ANP serum levels correlated to CpG methylation of the respective gene promoters on days 1, 7, and 14 of tobacco withdrawal. Results and Conclusion: Compared to non-smokers, promoter-related deoxyribonucleic acid methylation of the ANP promoter was significantly elevated on days 7 and 14 of withdrawal in tobacco-dependent patients. Baseline methylation status of the ANP promoter was not significantly different from controls, arguing for an impaired regulation during withdrawal.